"BRAND REPUTATION AND ITS EFFECT ON CONSUMER TRUST AND PURCHASE INTENTIONS IN E-COMMERCE" (CAHIERS MAGELLANES-NS, 2024)
Purpose: The abstract explores the profound impact of brand reputation on consumer trust and purchase intentions in e-commerce.Methodology: The study delves into the intricate interplay between brand reputation, consumer trust, and loyalty, utilizing comprehensive data analysis techniques including word cloud analysis, TF-IDF analysis, and topic modeling.Findings: Through the analysis, the research uncovers rich insights into the nuanced dynamics of brand reputation and its influence on consumer behavior. Key themes and factors associated with brand reputation in online shopping are identified, shedding light on the underlying drivers of consumer perceptions and decision-making processes.Conclusions: The findings have significant implications for marketers and e-commerce businesses, emphasizing the importance of prioritizing brand reputation as a strategic asset to drive sales, foster long-term loyalty, and enhance competitive advantage in the digital landscape.